IBADAH PERTOBATAN DAN TRANSFORMASI IBADAH: STUDI EKSEGESIS MAZMUR 51:16-19 - Rosalinda Samba’ Langi’; Mikael Randa Karaeng; Deventi Krislia Panggalo (CV. ADIBA AISHA AMIRA, 2026)
This study explores the concept of repentance and the transformation of worship in Psalm 51:16-19 through an exegetical approach. The central issue addressed is how the statement that God does not delight in sacrifice but in a broken and contrite heart can be properly understood within its theological and historical context, and how it informs contemporary worship practices. The research employs a qualitative interpretive method, integrating linguistic-semantic analysis of the Hebrew text, literary-structural examination, and historical-critical insights, along with theological reflection. The primary data is derived from the Hebrew text of Psalm 51:16-19, while secondary sources include biblical commentaries and theological literature on repentance and worship. The exegesis reveals that the passage criticizes superficial worship by emphasizing linguistic cues such as repeated imperatives and chiastic structures, which highlight the necessity of sincere repentance rather than mere ritual sacrifice. Instead, the text emphasizes inner transformation as the core of authentic worship. Furthermore, the study identifies a dynamic movement from empty ritual to restored worship grounded in a renewed relationship with God. This research concludes that Psalm 51:16-19 presents worship as a relational and transformative response rooted in repentance, offering a theological framework that challenges formalistic tendencies and reorients contemporary worship toward authenticity and life transformation.